2014
DOI: 10.1371/journal.pone.0086507
|View full text |Cite
|
Sign up to set email alerts
|

IHF Is Required for the Transcriptional Regulation of the Desulfovibrio vulgaris Hildenborough orp Operons

Abstract: Transcriptional activation of σ54-dependent promoters is usually tightly regulated in response to environmental cues. The high abundance of potential σ54-dependent promoters in the anaerobe bacteria, Desulfovibrio vulgaris Hildenborough, reflects the high versatility of this bacteria suggesting that σ54 factor is the nexus of a large regulatory network. Understanding the key players of σ54-regulation in this organism is therefore essential to gain insights into the adaptation to anaerobiosis. Recently, the D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Although the sequences shared only 30% identity, the structures were superimposable (Cort, Yee, Edwards, Arrowsmith, & Kennedy, 2000). A similar domain was found to be encoded in three members of a divergent set of co-regulated genes in D. vulgaris (Fiévet, Cascales, Valette, Dolla, & Aubert, 2014;Fiévet et al, 2011). Further exploration showed that proteins with this COG shared homology with a protein from D. gigas that had been described earlier as the "orange protein" (ORP) (George et al, 2000).…”
Section: Anaerobic Growthmentioning
confidence: 75%
“…Although the sequences shared only 30% identity, the structures were superimposable (Cort, Yee, Edwards, Arrowsmith, & Kennedy, 2000). A similar domain was found to be encoded in three members of a divergent set of co-regulated genes in D. vulgaris (Fiévet, Cascales, Valette, Dolla, & Aubert, 2014;Fiévet et al, 2011). Further exploration showed that proteins with this COG shared homology with a protein from D. gigas that had been described earlier as the "orange protein" (ORP) (George et al, 2000).…”
Section: Anaerobic Growthmentioning
confidence: 75%
“…These results suggest that the gene duplication present in the Deltaproteobacteria is very ancient but occurred after the separation of the Gamma and Deltaproteobacteria lineages. D. vulgaris H is the only Deltaproteobacteria in which the role of IHF has been studied; in this organism, IHF participates in the expression of the orp genes involved in cell division ( Fiévet et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The canonical structure of IHF consists of two paralogous subunits, IHFα and IHFβ, encoded by the unlinked ihfA and ihfB genes ( Haluzi et al, 1991 ; Weisberg et al, 1996 ). Among other roles, IHF is required for the activation of genes transcribed by RpoN-containing RNA polymerase ( Cannon et al, 1990 ; Hoover et al, 1990 ; de Lorenzo et al, 1991 ), including those participating in nitrogen fixation in Klebsiella pneumoniae , alginate synthesis in Pseudomonas aeruginosa , regulation of flagella genes in Caulobacter crescentus , toluene degradation in Pseudomonas putida , and cell division in Desulfovibrio vulgaris Hildenborough ( Cannon et al, 1990 ; Santero et al, 1992 ; Calb et al, 1996 ; Delic-Attree et al, 1996 ; Muir and Gober, 2005 ; Fiévet et al, 2014 ). Upon binding, IHF bends the DNA, promoting the interaction between the bound upstream activator, EBP with the RpoN-RNA polymerase ( Morett and Segovia, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ORP complex is made of 5 proteins named Orp3 (DVU2103), Orp4 (DVU2104), Orp5 (DVU2105), Orp8 (DVU2108) and Orp9 (DVU2109), putatively involved in cell division 19 . The genes coding for ORP proteins are clustered into two divergent operons whose expression is controled from a σ 54 -dependent promoter 19,20 . Most of the ORP proteins are predicted to be metal binding proteins.…”
Section: Introductionmentioning
confidence: 99%